2012
DOI: 10.1051/epjconf/20122900016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of lanthanum monoaluminate by co-precipitation method

Abstract: Abstract.Our contribution has focused on the synthesis and characterization of lanthanum monoaluminate LaAlO3 by the method of co-precipitation. The powder was successfully synthesized using NaOH, La (NO 3 ) 3 .6H 2 O and Al (NO 3 ) 3 .9H 2 O as raw materials by this method and calcined at different temperatures. It was characterized by several techniques: Fourier transform infrared spectroscopy (FT-IR), thermogravimetric and differential thermal analysis (TGA/DTA), X-ray diffraction (XRD) and laser diffusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…. Our study shows the high reactivity of -Al 2 O 3 with La 2 O 3 or its precursors (such as La hydroxide, nitrate or oxynitrate), producing LaAlO 3 at 1023 K. Previous studies indeed showed that crystallization of LaAlO 3 can occur already at 873 K from co-precipitated powders59 , although usually higher temperatures are needed (973-1173 K60,61 ), but their formation seems much easier than that of LaAl 11 O 18 and of -Al 2 O 3 , which occur at higher temperature62 .These findings indicate that even small amounts of Lanthana indeed tend to stabilize -Al 2 O 3 against sintering and loss of surface area (samples 5LaA and 20LaA), as it has been reported by several studies3,4 . The formation of bulk lanthanum-containing phases can instead cause the reaction of -Al 2 O 3 at moderate temperatures, with the formation of bulk LaAlO 3 , and an important decrease of surface area.Characterization data show that the 80LaA sample is largely dehydroxylated by outgassing at 773 K and fully lost the strong Lewis acidity of alumina.…”
supporting
confidence: 64%
“…. Our study shows the high reactivity of -Al 2 O 3 with La 2 O 3 or its precursors (such as La hydroxide, nitrate or oxynitrate), producing LaAlO 3 at 1023 K. Previous studies indeed showed that crystallization of LaAlO 3 can occur already at 873 K from co-precipitated powders59 , although usually higher temperatures are needed (973-1173 K60,61 ), but their formation seems much easier than that of LaAl 11 O 18 and of -Al 2 O 3 , which occur at higher temperature62 .These findings indicate that even small amounts of Lanthana indeed tend to stabilize -Al 2 O 3 against sintering and loss of surface area (samples 5LaA and 20LaA), as it has been reported by several studies3,4 . The formation of bulk lanthanum-containing phases can instead cause the reaction of -Al 2 O 3 at moderate temperatures, with the formation of bulk LaAlO 3 , and an important decrease of surface area.Characterization data show that the 80LaA sample is largely dehydroxylated by outgassing at 773 K and fully lost the strong Lewis acidity of alumina.…”
supporting
confidence: 64%
“…FTIR is a way out solution for the determination of various bonds and atoms present in organic or inorganic samples. Infrared spectrum of a molecule is produced only when the natural frequency of vibration of atoms matches the frequency of incident radiation [37,38]. After absorbing the correct wavelength of radiation, the molecule starts vibrating and gives a characteristic peak.…”
Section: Characterizationmentioning
confidence: 99%
“…Also, this sharper peak is known to by reason of the existence of stretching vibration of Fe-O approves the octahedral FeO 6 existence in the structure. Therefore, it is better to underline here that in the literature, especially in case of the "700-400 cm -1 " region of the IR spectrum, it is well-known that peaks may be attributed to the characteristic Metal-Oxygen bond vibrations for the perovskite structure compounds [18]. https://doi.org/10.35193/bseufbd.975808…”
Section: Table 1 Textural Properties Of the Lsafsmentioning
confidence: 91%